Singapore : Selected Issues. (IMF Staff Country Reports; Country Report, 2013)
This Selected Issues Paper discusses some observations on Singapore's monetary policy framework. Singapore's monetary policy uses the nominal effective exchange rate (NEER) as the instrument in a basket-band-crawl framework. The paper finds that under some conditions an exchange rate-based monetary policy may not be detrimental to external competitiveness. A key parameter is the weight of imports in the consumer basket or production function. Tightening monetary policy through a nominal appreciation helps to dampen imported cost pressures. In addition, nominal appreciation can reduce domestic sources of inflation by lowering demand for local factors of production.